Efficacy of Targeted Mist-Netting to Capture Northern Bobwhites During the Non-Breeding Season in Ohio - Mark J. Wiley; Adam K. Janke; Robert J. Gates (National Quail Symposium Proceedings, 2017)
Baited funnel traps and nightlighting are well established northern bobwhite (Colinus virginianus) capture techniques, but their use is not always appropriate, particularly on private land where cooperating landowners may place constraints on research activities. Alternative capture techniques may be more effective under conditions considered to be unfavorable for established techniques (e.g., periods with abundant natural food). Targeted mist-netting, where mist nets are erected near the known location of specific individuals, has been used to capture gallinaceous species and may be an effective alternative to established bobwhite capture techniques. We evaluated the effectiveness of using targeted mist-netting to capture bobwhites during the non-breeding season in Ohio. We tested for differences in survival and age and sex ratios of individuals captured with targeted netting and baited funnel traps. We captured 257 individuals with targeted netting during 1 October-28 February 2009–2011 and concurrently captured 253 individuals with baited funnel traps. There was a short-term influence of capture and handling, but there was no significant difference in post-capture survival of bobwhites captured with targeted netting or trapping. Capture rates of age and sex classes were similar (P 1⁄4 0.488 and P 1⁄4 0.973, respectively) between targeted netting and trapping. Body mass of bobwhites captured by targeted netting was less than that of bobwhites captured by trapping (P 1⁄4 0.009) suggesting that netting may provide more accurate estimates of body mass. We used targeted netting to capture bobwhites in a variety of situations where use of funnel traps was ineffective or problematic. Targeted netting was effective and often more compatible with constraints of working on private land than established capture techniques.
Keywords: capture techniques; Colinus virginianus; mist netting; northern bobwhite; Ohio; private land; Program MARK; radiotelemetry; survival; trapping